The community foundations model in México : An approach from the perspective of commons - Guadarrama Sánchez, Gloria Jovita (Cooperativismo & Desarrollo, 2019)
The aim of the study is to explore the Mexican community foundations model from the perspective of associative goods. After the outlines of theoretical propositions about the nature of social goods, particularly the notion of commons, the experience of Mexican foundations model is revisited. The analysis views the goods generated by the participation of the members of foundations and make distinctions about the goods result of community collective action like relations that can not be reduced to the interchanges with the market or the state. The deliberation shows that community foundations are spaces of inner and external integration and development of different goods.